Tradisi Malam Hela-Hela di Desa Kema III Kecamatan Kema Kabupaten Minahasa Utara (Studi Antropologi Agama) - Mutiara Rauf; Maria Heny Pratiknjo; Titiek Mulianti (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
This study examines the Hela-Hela night tradition in Kema III Village, North Minahasa Regency, as a culturally embedded religious practice performed on the 27th night of Ramadan to commemorate Lailatul Qadar. The research aims to explore the history, symbolism, community perception, and cultural transformation of the Hela-Hela tradition through the lens of religious anthropology. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The findings reveal that this tradition has historical roots in the cultural spread of Islam along coastal regions and integrates religious meanings with social values through symbols such as bananas, oil-bottle lanterns, and bamboo ropes. Changes in ritual practice reflect social dynamics while preserving the spiritual essence of the tradition. Community interpretations vary across generations, yet collective participation remains strong. The Hela-Hela tradition functions as a medium for internalizing religious values, fostering social solidarity, and reaffirming communal identity. This study highlights the strategic role of local religious practices in sustaining cultural resilience and communal spirituality amid the tides of modernity